PELATIHAN INSPEKSI VISUAL PENGELASAN SMAW (LAS BUSUR LISTRIK) UNTUK WARGA RW 24 NOTOYUDAN, PRINGGOKUSUMAN, GEDONGTENGEN, YOGYAKARTA - Ellyawan Setyo Arbintarso; Agus Duniawan (DHARMA BAKTI, 2019)
Sheilded Metal Arc Welding (Electric arc) welding has been widely used by the public and produces various types of weld products. This type of welding is the choice of the community because the equipment is easily available and relatively affordable. Knowledge of welding results is still minimal mastered by the community so training is needed to understand how to inspect or check welding results. Visual inspection is the easiest way only with the naked eye or using a magnifying glass, this examination can be done. Although simple, visual inspection is very helpful in controlling the quality of welds. Visual inspection can detect 9 types of defects that occur due to the welding process using an electric arc.